ANALISIS HUBUNGAN LAJU INFLASI, REALISASI INVESTASI INDUSTRI KECIL, PEROLEHAN PAD, PENYERAPAN TENAGA KERJA TERHADAP PENDAPATAN PERKAPITA (Studi Kasus di Kabupaten Nganjuk) - Rony Kurniawan; Edy Djoko Soeprajitno (JURNAL AKUNTANSI DAN MANAJEMEN MUTIARA MADANI, 2016)
The results of this study independent variable inflation rate has no effect on the dependent variable per capita income. This corresponds with the results of Persia test (t test) -0.381255 with a probability value of 0.716. Variable investment informal sector mention significantly affect the per capita income of the people Nganjuk district. This is evident from the figures show positive investment coefficient of 2.983050, with a probability of 0.02 is far below the level of 0.05 is the standard threshold siginifikansi in this study. Similarly, the variable revenue (PAD) has a significant relationship to the per capita income of mesayarakat in Nganjuk. This can be seen from the partial test (t test) with numbers koefeisien 3.915228 probability value of 0.0078.But the independent variable Employment in small industry sector did not affect the per capita income of the people in Nganjuk. This assumption is based on the probability of regression of 0.1727 which shows much of the research siginifikansi threshold is set at figure 0.05. This study uses linear regression analysis using model test beganda and Error Correction Model (ECM) to test the residue so that it can create the best coefficient least unbyas estimate (blue) as a condition of regression can be estimated. Data used in the study of time series of inflation rate, the realization of PAD Nganjuk, realization of investment in small industrial sector, employment in the informal sector in Nganjuk and per capita income from 2002 to 2013 period.